Creation made into הָמְכָח: The eco-theological appraisal of the intrinsic worth of nature in Proverbs 3:19–20 - Kavusa, Jonathan (Stellenbosch Theological Journal, 2018)
This article explores the statement “creation made in wisdom” of Proverbs 3:19–20 as pointing to the Earth Bible’s principle of intrinsic worth/value of nature. This article argues that our contemporary societies need to adjust their development in harmony with the cosmic order as secured by God at creation through wisdom. Wisdom in creation constitutes the supreme ideal for living wisely, and for constructing a healthy society that is in harmony with creation.